A Surprising Source of Self-Motivation: Prior Competence Frustration Strengthens One’s Motivation to Win in Another Competence-Supportive Activity - Fang, Hui; He, Bin; Fu, Huijian; Zhang, Huijun; Mo, Zan; Meng, Liang (Frontiers in Human Neuroscience, 2018)
According to self-determination theory, competence is among the three basic psychological needs essential for one’s well-being and optimal functioning, and the frustration of these needs is theoretically predicted to induce a restorative response. While previous studies have explored the restoration process for autonomy and relatedness, empirical evidence for such a process is still lacking for competence. In order to explore this process and to examine the effect of prior competence frustration on one’s motivation to win in a subsequent competence-supportive task, we adopted a between-group experimental design and manipulated one’s competence frustration through task difficulty in an electrophysiological study. Participants in both groups were instructed to work on different tasks in two successive sessions respectively. Participants in the experimental group were asked to complete a highly difficult task in the first session and a task of medium difficulty in the second session, while those in the control group were instructed to finish tasks of medium difficulty in both sessions. In the second session, an enlarged feedback-related negativity loss-win difference wave (d-FRN) was observed in the experimental group compared to the control group, indicating that they have an enhanced motivation to win in a subsequent competence-supportive task. Thus, results of the present study provided original neural evidence for the restoration process of the basic psychological need of competence.